COORDINATION DEVELOPEMENT FOR AUTISTIC CHILDREN THROUGH SWIMMING MEANS - Oana Paţa; Elena Rata (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The paper aims to demonstrate the beneficial role it has swimming, in coordinative capacity development, specially balance, space orientation and mobility, to children with autism. By applying a swimming program tailored especially appropriate an 8 year old, a child diagnosed with autism, it aims to develop coordinative capacity indicators, balance, spatial-temporal orientation and mobility.